2013
DOI: 10.12659/ajcr.889290
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral gangrene: A rare presentation of systemic lupus erythematosus in a child

Abstract: Patient: Female, 12Final Diagnosis: Antiphospholipid positive SLESymptoms: Gangrene • Raynaud’s phenomenon • autoamputation of the terminal phalanx of the second left hand fingerMedication: Prednisolone • mycophenolate mofetil • captoprilClinical Procedure: Renal Biopsy • treatment of lupus nephritis • control of hypertensionSpecialty: Pediatric rheumatologyObjective:Unusual clinical courseBackground:SLE in children has many manifestations. In several studies on SLE in children, gangrene and Raynaud phenomenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…A study involving 50 adult female SLE patients found that the individuals who developed cutaneous vasculitis were younger when compared to patients who did not develop vasculitis [11]. SLE vasculitis and related digital gangrene can be treated with a variety of drugs, and drug combinations include corticosteroids, immunosuppressant drugs such as mycophenolate mofetil [12], and monoclonal antibodies such as rituximab. According to a study done by Liu et al on 2684 patients with SLE showed Raynaud's phenomenon (RP), elevated serum C-reactive protein (CRP), and lengthy disease duration (> or equal to 4 years) all increased the risk of developing digital gangrene and early treatment with steroids (prednisone > or equal to 1mg/kg/d started within 3 weeks) signi cantly reduced the risks of amputation [13].…”
Section: Discussionmentioning
confidence: 99%
“…A study involving 50 adult female SLE patients found that the individuals who developed cutaneous vasculitis were younger when compared to patients who did not develop vasculitis [11]. SLE vasculitis and related digital gangrene can be treated with a variety of drugs, and drug combinations include corticosteroids, immunosuppressant drugs such as mycophenolate mofetil [12], and monoclonal antibodies such as rituximab. According to a study done by Liu et al on 2684 patients with SLE showed Raynaud's phenomenon (RP), elevated serum C-reactive protein (CRP), and lengthy disease duration (> or equal to 4 years) all increased the risk of developing digital gangrene and early treatment with steroids (prednisone > or equal to 1mg/kg/d started within 3 weeks) signi cantly reduced the risks of amputation [13].…”
Section: Discussionmentioning
confidence: 99%
“…There are many drugs that can be used to treat SLE vasculitis and related digital gangrene. Some of these are corticosteroids, immunosuppressant drugs like mycophenolate mofetil [ 14 ], and monoclonal antibodies like rituximab. A study by Liu et al looked at 2,684 SLE patients and found that Raynaud's phenomenon (RP), high serum C-reactive protein (CRP), and having the disease for more than four years all made it more likely that the patients would get digital gangrene.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac vasculitis in JSLE typically comprises pericarditis, cardiomegaly, valvulitis, and conduction abnormalities. The most common causes of extremity gangrene in SLE are APS and endarteritis [ 11 ]. Differentiating vasculopathy/thrombosis and vasculitis in SLE-associated APS can be difficult and requires histological assessment of cutaneous lesions.…”
Section: Discussionmentioning
confidence: 99%